Determination of Factors Influence Customer Satisfaction at BMT Syariah Sejahtera Boyolali - Khotijah Arum; Yuni Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The COVID-19 pandemic became a major problem for BMT because it restricted interaction with customers. Therefore, trust in BMT also decreased. This study aimed to assess customer satisfaction of BMT Syariah Sejahtera Boyolali used service quality, trust, and customer value. The population in this study were regular customers of the BMT Syariah Sejahtera Boyolali. The questionnaires were distributed to 109 BMT customers. The data tested by validation tests, reliability tests, tests of classical assumptions, and multiple linear regression analysis. The findings indicated that customer trust and value significantly influenced customer satisfaction. However, service quality didn't influence to customer satisfaction.